THE EFFICACY OF BIOPHARMACEUTICALS IN DISEASE MANAGEMENT - Nasser Mubarek Aldosary, Fahad Mohammad Alsaleh, .Abdullah Jarallah Alghammas, .Abdulaziz Mohammed Binkhider, .Naif Asaad Aljashaam, Ahmed Ageel Alassaf, Mohammed Yahya Abutalib, Salem Mazhor Aldosary,; Abdullah Hassan Alruwaite, Tariq Salem Mubarak Aldosary, Ahmad Noman Alsaleh (Chelonian Research Foundation, 2022)
Biopharmaceutical medications, which were first introduced in 1982, have significantly transformed the treatment of a wide range of disorders and are now being used in almost every field of medicine. The biopharmaceuticals market has had rapid expansion in recent years, surpassing the overall medicine market. It is expected to continue growing dynamically because to the high demand for these treatments. Biobetters, which consist of modified active pharmaceutical components that exhibit improved effectiveness, will have a significant impact on the advancement of biopharmaceuticals. Biosimilars are another important category of biopharmaceuticals. Their entry into the European Union and, more recently, the United States markets will result in decreased costs for biopharmaceutical therapy. This study focuses on the latest advancements in the area of biopharmaceutical research and the challenges related to the approval of novel biopharmaceuticals and biosimilars. This text discusses the primary category of biopharmaceuticals, the present state of the biopharmaceuticals market, and predictions for the future. Keywords: biopharmaceuticals, disease management, biosimilars, drug market, challenges.